Laser‐Induced Molybdenum Carbide–Graphene Composites for 3D Foldable Paper Electronics. Issue 26 (15th May 2018) - Zang, Xining; Shen, Caiwei; Chu, Yao; Li, Buxuan; Wei, Minsong; Zhong, Junwen; Sanghadasa, Mohan; Lin, Liwei
Abstract: Versatile and low‐cost manufacturing processes/materials are essential for the development of paper electronics. Here, a direct‐write laser patterning process is developed to make conductive molybdenum carbide–graphene (MCG) composites directly on paper substrates. The hierarchically porous MCG structures are converted from fibrous paper soaked with the gelatin‐mediated inks containing molybdenum ions. The resulting Mo3 C2 and graphene composites are mechanically stable and electrochemically active for various potential applications, such as electrochemical ion detectors and gas sensors, energy harvesters, and supercapacitors. Experimentally, the electrical conductivity of the composite is resilient to mechanical deformation with less than 5% degradation after 750 cycles of 180° repeated folding tests. As such, the direct laser conversion of MCGs on papers can be applicable for paper‐based electronics, including the 3D origami folding structures. Abstract : A direct‐write laser‐patterning process to induce molybdenum carbide–graphene composites on paper substrates is developed by using inks of molybdenum ions and gelatin media with potential applications in 3D foldable energy generators, electrochemical sensors, and supercapacitors.